Chronic disease prevalence among elderly Saudi men - Saquib, Nazmus; Saquib, Juliann; Alhadlag, Abdulrahman; Albakour, Mohamad Anas; Aljumah, Bader; Sughayyir, Mohammed; Alhomidan, Ziad; Alminderej, Omar; Aljaser, Mohamed; Al-Mazrou, Abdulrahman (International Journal of Health Sciences, 2017)
Objective: Saudi demographic composition has changed because of increased life expectancy and decreased fertility rates. Little data are available about health conditions among older adults in Saudi Arabia, who are expected to represent 20% of the population by 2050. The study aim was to assess the prevalence and risk factors for chronic conditions among older Saudi men. Methods: The sample pertained to 400 men (age ≥55 years) from Buraidah, Al-Qassim. Research assistants recruited participants in all the mosques from the randomly selected neighborhoods (16 of 95). They administered a structured questionnaire that assessed self-reported disease history (heart disease, hypertension, diabetes, asthma, gastric/peptic ulcer, and cancer), and medication use; participants’ height, weight, blood pressure, and random blood glucose (glucometer) were measured. Multinomial logistic regressions were employed to assess correlates of number of chronic diseases. Results: The mean and standard deviation for age and body mass index (BMI) were 63.0 ± 7.5 years and 28.9 ± 4.8 (kg/m2), respectively. 78% (77.8%) were overweight or obese, 35.0% were employed, 54.5% walked daily, 9.3% were current smokers, and 85.0% belonged to the middle class. The prevalence of hypertension, diabetes, heart disease, asthma, ulcer, and cancer were: 71.3% 27.3%, 16.4%, 9.7%, 8.9%, and 2.0%, respectively. Of the participants, 31.0% had one, 34.5% had two or more, and 34.5% did not have any chronic diseases. The likelihood of chronic diseases increased with increased age, higher BMI, and current smoking. Conclusion: The chronic disease prevalence among the Saudi elderly men is substantial.